Competency Improvement Training in Compiling Final Thesis Assignments - Putri Ida; Wahrini, Retyana; Ganggang Canggi Arnanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Thesis Writing Training for 6th Semester Students of the Electronic Engineering Education Study Program, FT UNM aims to improve students' competence and confidence in writing their theses. The training was held for two days, covering an explanation of the structure of the thesis, research methodology, and the application and ability to manage references effectively is also an important aspect in writing student theses. However, many students still face obstacles in reference management, especially in compiling consistent citations and bibliographies that are in accordance with the format. The evaluation of the activity showed that the majority of students felt helped and more confident in facing the thesis writing process. Active interaction during lectures and group discussions provided practical solutions to problems faced by students and increased their motivation. Thus, this training succeeded in supporting students in achieving optimal academic achievement in accordance with applicable academic standards. The positive impact of this program is expected to support students in compiling theses with better quality and reducing citation errors. The recommendation for the sustainability of this program is to hold similar training periodically to improve students' reference management skills.